2022
DOI: 10.2337/dc21-1864
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Type 2 Diabetes in Individuals With a Psychiatric Disorder: A Nationwide Register-Based Cohort Study

Abstract: OBJECTIVE Previous studies have investigated the incidence of type 2 diabetes in individuals with psychiatric disorders, but most studies have focused on a specific psychiatric disorder or a selected sample. More population-based studies are needed to determine these associations in representative samples. We therefore aimed to determine these associations in a nationwide, register-based dynamic cohort study. RESEARCH DESIGN AND METHODS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…For the association of psychiatric disorders and subsequent T2DM, our results replicate previous findings of increased risk of T2DM in individuals with psychiatric disorders, including substance use disorder, schizophrenia, depression, bipolar disorder, personality disorder, and ADHD, all with similar effect sizes as ours, despite a younger cohort in our study and differences in T2DM definitions [13,14,17,41]. Our study also adds to the literature by demonstrating significant positive associations of other specific psychiatric disorders, namely OCD, ASD, other (non-anorectic) eating disorders, and anxiety, with subsequent diagnoses of T2DM.…”
Section: Temporal Order Of T2dm and Brain Disorderssupporting
confidence: 90%
See 2 more Smart Citations
“…For the association of psychiatric disorders and subsequent T2DM, our results replicate previous findings of increased risk of T2DM in individuals with psychiatric disorders, including substance use disorder, schizophrenia, depression, bipolar disorder, personality disorder, and ADHD, all with similar effect sizes as ours, despite a younger cohort in our study and differences in T2DM definitions [13,14,17,41]. Our study also adds to the literature by demonstrating significant positive associations of other specific psychiatric disorders, namely OCD, ASD, other (non-anorectic) eating disorders, and anxiety, with subsequent diagnoses of T2DM.…”
Section: Temporal Order Of T2dm and Brain Disorderssupporting
confidence: 90%
“…Across the lifespan, T2DM is associated with increased risks for adverse health outcomes, such as cardiovascular diseases, and premature death [7][8][9]. Studies have also found associations between T2DM and disorders of the brain, including vascular dementia and Alzheimer's disease [10], substance use disorder, schizophrenia, bipolar disorder, depression, personality disorder, and attention-deficit/ hyperactivity disorder (ADHD) [11][12][13][14][15][16][17], obsessive-compulsive disorder (OCD) [18], cognitive impairment [19], and also of filling a prescription for psychotropic drugs, including antidepressants, antipsychotics, and anxiolytics [20]. Recently, the term "insulinopathies of the brain" has been suggested to characterize these associations between T2DM and brain disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is required to understand the dynamics and patterns of management of patients with depression to improve outcomes for patients with diabetes and other comorbidities including depression. In addition, given the complexity of the roles of comorbidities in the interplay of diabetes and depression, detailed evaluation of the bidirectional association between these conditions in different ethnicities, age groups and sex is crucial [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The causes of T2DM are complex and socially mediated, with risk factors including but not limited to: being older; having a family history of or genetic predisposition to T2DM; being of Indigenous, African, Arab, Hispanic, or South Asian descent; living with overweight or obesity; being physically inactive; having a lower level of education or socioeconomic status; having an unhealthy diet; living with psychological stress, mental illness, or social isolation; and exposure to air and noise pollution. 1,[4][5][6][7][8][9][10] Persistent hyperglycemia may cause short-and long-term complications associated with decreased quality of life and, in some cases, early death. [11][12][13][14] In the short term, hyperglycemia can cause excessive urination, thirst, weight loss, increased risk of infection, and neurologic symptoms.…”
Section: Introductionmentioning
confidence: 99%